Pengaruh Penambahan Variasi Karagenan Terhadap Sifat Mekanik Edible film dari Pati Bengkuang (Pachyrhizus Erosus) - Anaka, Dego Taftazani; Dewata, Indang (Universitas Negeri Padang, 2022)
Edible film is a thin plastik with a thickness of less than 0.25 mm which is often used to protect food products. This study aims to determine the effect of adding variations of carrageenan to the mechanical properties of edible film from yam starch. This research used polyethylene glycol (PEG) plastikizer and carrageenan variations (0.5%, 1%, 1.5% and 2%). The resulting edible film was analyzed for its mechanical properties. The higher the addition of carrageenan concentration, the thicker the edible film produced, and the maximum yield was obtained at the tensile strength of 2.92 Mpa and elasticity 7.02 Mpa at the addition of 1% carrageenan, the minimum elongation value of 0.41% at the addition of 1% and 1.5% carrageenan. The results of this study indicate that the addition of carrageenan variations affects the mechanical properties of the edible film.